MODEL MANAJEMEN EDU–FINANCE UNTUK MENINGKATKAN LITERASI KEUANGAN PADA UMKM KAYU KOTA SEMARANG - C. Tri Widiastuti; Aprih Santoso (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2017)
This study aims to analyze the implementation of financial management that has been done and design edu-finance management model to improve financial literacy on the perpetrators of wood SMEs Semarang City. The research used qualitative method, data collecting technique through in-depth interview. Sample of data source include wood wooden perpetrator at Jl. Barito, Central Java Bank as a distributor of SMEs credit in Semarang City, and Head of Institutional Affairs Office of Cooperatives and SMEs of Central Java Province. Data analysis techniques using Miles and Hubermans model. Test the validity of data with credibility test through extension of observation and triangulation. The results revealed that the perpetrators of wood SMEs on Jl. Barito Semarang does not yet have sufficient knowledge related to financial literacy. Increased understanding of financial literacy required a training model that fits the needs that include: financial management, financing and entrepreneur. Training strategy is done by planning, implementation and evaluation of financial literacy training. It needs integrated training, comprehensive and sustainable. Stakeholders are expected to engage SMEs actors in making policies so that the policies made can be more implemented in the field. Keywords: Financial Literacy, Edu-Finance, SMEs